MEDIA CULTURE IN DIFFERENT APPROACHES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article describes different approaches to understanding media culture. In particular, philosophical, cultural, informational, pedagogical, attributive, socio-psychological approaches and their content are covered.